Instantaneous expansion with a single fracture: A new directional rock-breaking technology for roof cutting. (August 2020) - Zhang, Quan; He, Manchao; Wang, Jiong; Guo, Shan; Guo, Zhibiao; Liu, Xiaoyu; Hu, Jinzhu; Ma, Zimin; Fan, Lanxiang; Guo, Pengfei
Abstract: Directional roof-cutting with shaped charge blasting is dangerous and produces large vibrations. Accordingly, a new, nonexplosive method known as instantaneous expansion with a single fracture (IESF) has been developed and tested in the field. This method uses a slit-oriented pipe and a special slitting agent triggered by electric current without a detonator. It is capable of producing a single crack that propagates through the rock in a selected direction. The mechanism of directional roof-cutting using IESF is analyzed, and the conditions for directional crack initiation and propagation are presented. The new technique has been successfully applied to directional roof-cutting in an actual coal mine. It resulted in a larger crack rate, a smaller charge, reduced vibration, and an improved safety profile than shaped charge blasting. IESFs are a substitute for explosives and are expected to have broad application prospects in directional rock breaking.